2009
DOI: 10.1016/j.dnarep.2009.07.011
|View full text |Cite
|
Sign up to set email alerts
|

NUDT5 hydrolyzes oxidized deoxyribonucleoside diphosphates with broad substrate specificity

Abstract: The human NUDT5 protein catalyzes the hydrolysis of 8-hydroxy-dGDP. To examine its substrate specificity, four oxidized deoxyribonucleotides (2-hydroxy-dADP, 8-hydroxy-dADP, 5-formyl-dUDP, and 5-hydroxy-dCDP) were incubated with the NUDT5 protein. Interestingly, all of the nucleotides, except for 5-hydroxy-dCDP, were hydrolyzed with various efficiencies. The kinetic parameters indicated that 8-hydroxy-dADP was hydrolyzed as efficiently as 8-hydroxy-dGDP.The hydrolyzing activities for their triphosphate counter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…We also examined the proteins for a possible relationship between their primary structures and their ranges of substrate specificity. The three human proteins MTH1, MTH3, and NUDT5, as well as the S. cerevisiae protein Pcd1, can cleave various types of oxidized purine nucleotides, whereas the E. coli MutT and C. elegans NDX-1 proteins act strictly on 8-oxoGua-containing nucleotides (27,28,30), yet specific sequence motifs for distinguishing these two groups of proteins have not been identified. The substrate recognition and binding may be achieved by a few amino acid residues located near or within the active center, and thus, elucidation of the three-dimensional structures is essential for solving this problem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also examined the proteins for a possible relationship between their primary structures and their ranges of substrate specificity. The three human proteins MTH1, MTH3, and NUDT5, as well as the S. cerevisiae protein Pcd1, can cleave various types of oxidized purine nucleotides, whereas the E. coli MutT and C. elegans NDX-1 proteins act strictly on 8-oxoGua-containing nucleotides (27,28,30), yet specific sequence motifs for distinguishing these two groups of proteins have not been identified. The substrate recognition and binding may be achieved by a few amino acid residues located near or within the active center, and thus, elucidation of the three-dimensional structures is essential for solving this problem.…”
Section: Discussionmentioning
confidence: 99%
“…Actions of MTH3 on Other Types of Oxidized Nucleotides-It has been shown that the human MTH1 and NUDT5 proteins possess the ability to hydrolyze other types of oxidized nucleotides besides those containing 8-oxo-Gua (27,28). To determine whether MTH3 has such an activity, three types of oxidized nucleoside diphosphates were treated with MTH3, and the reaction products were analyzed by HPLC.…”
Section: Purification Of Enzymes Acting On Oxidized Guanine-containinmentioning
confidence: 99%
“…The broad substrate specificity of MTH1 suggests its versatile roles in multiple sanitization pathways. Furthermore, human NUDT5 specifically degrades 8-oxo-dGDP (Sekiguchi and Tsuzuki, 2002;Ishibashi et al, 2003;Kamiya et al, 2009). All of these proteins significantly suppress the mutator phenotype in mutT-deficient E. coli mutant cells (Ishibashi et al, 2003;Kamiya et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, human NUDT5 specifically degrades 8-oxo-dGDP (Sekiguchi and Tsuzuki, 2002;Ishibashi et al, 2003;Kamiya et al, 2009). All of these proteins significantly suppress the mutator phenotype in mutT-deficient E. coli mutant cells (Ishibashi et al, 2003;Kamiya et al, 2009). Thus, it is quite possible that other oxidized nucleotides with potent mutagenicity are continually generated by ROS in E. coli and eukaryotes, including C. intestinalis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation